The effect of liquid tumeric extract supplementation on carcass production and chemical quality of broiler meat - Hidayat, M.; Zuprizal, Z.; Sundari, S.; Kurniawati, A.; Wati, A. K.; Kusmayadi, A. (Journal of the Indonesian Tropical Animal Agriculture, 2017)
The purpose of this research was to find out the effects of liquid turmeric extract (LTE) supplementation as a phytobiotic on carcass production and chemical quality of broiler chicken meat. The research is conducted with a directional pattern completely randomized design. Eighty-four broiler chickens were raised from day old (DOC) to 42 days old chick. From DOC to 14 days old chicks were fed with commercial feed (ME 3,100 kcal/kg; CP 22%; Ca 1%; P 0.75%). During 15-21 days of age given a commercial feed mixture and basal feed (ME 3,201.77 kcal/kg; CP 20.21%; Ca 0.90%; and P 0.43%). At 22-42 days old given treatments. Seven treatments were replicated 3 times consisted of 4 broiler chickens for each replication. The treatments were positive control (P1), negative control (P2), water + LTE 2% (P3), water + LTE 4% (P4), water + LTE 6% (P5), water + LTE 8% (P6), and water + LTE 10% (P7). The results showed that LTE 10% significantly decreased (P<0.05) on the slaughter weight and 8% until 10% dossage had a significant decrease (P<0.05) on the meat water content. However, it did not show a significant influence (P>0.05) on the carcass weight, carcass percentage, meat protein and fat content.